MUSIC IN HUMAN LIFE: ANTHROPOLOGICAL PERSPECTIVES ON MUSIC, by John E. Kaemmer, University of Texas Press, 1993, ISBN 0 292 74314 9, 245pp, b/w plates, musical examples, diagrams, glossary, index. - Kruger, Jaco (International Library of African Music, 1996)
pages: 117-119
Keywords: African Music